On the Stability of Synthetic CDO Credit Ratings. (8th June 2016) - Zapata, Javier; Cifuentes, Arturo
Abstract: Synthetic collateralized debt obligations (CDOs) performed very badly during the subprime crisis: they suffered massive rating downgrades (even at the most senior levels of the capital structure) and inflicted significant losses on investors. Using numerical simulations, this study shows that such structures are highly unstable; minor errors in the basic assumptions could manifest dramatically in the accuracy of CDO rating calculations. Regardless of the quality of the underlying assets, it is impossible to make reliable statements regarding the future performance of a synthetic CDO tranche. Moreover, this study demonstrates that single‐point credit risk estimators (in which no attempt at specifying a confidence interval is made) could be especially misleading. Finally, the study suggests that a regulatory framework based on credit ratings as they are presently defined is unlikely to be effective.